Pengaruh Konfigurasi Politik Terhadap Produk Hukum Pada Masa Pemerintahan Soeharto Di Indonesia - Wasti, Ryan Muthiara (Jurnal Hukum & Pembangunan, 2015)
Soeharto government becomes an interesting theme for nearly every research because of the uniqueness of the rule known as the authoritarian nature. However, the uniqueness is only studied until the result of the authoritarian who has raised the swelter of almost all the people and eventually led to the cessation of Soeharto as the head of the State Indonesia. Yet seen from the eyes of the law, the political transition in the future not only of political influence, but also legally so as to distinguish between authoritarian rule and democratic governance. This study will address these problems are divided into two: the first part will look at the political configuration that occurred in Indonesia during the transition from Sukarno government towards the Soeharto government, and the second part will analyze the form of a legal product that is formed from the political configuration that was built after the The transition compared to the legal product before and after the transition period. With two issues are expected to show how a head of state will govern affect measures taken shape, which certainly will be poured in the form of legislation. Tentative conclusions is that there is significant influence between the political configuration with legal products produced by the legislature during the reign of the.